2020
DOI: 10.1038/s41598-020-76894-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tightness of the hip joint and shoulder/elbow injury in high school baseball pitchers: a prospective study

Abstract: Some studies have reported that upper limb tightness is a risk factor for shoulder/elbow pain in high school baseball pitchers; but there has been insufficient research on the relationship between lower limb tightness and shoulder and elbow pain in pitchers. This study aimed to clarify the correlation among pre-season hip range of motion (ROM) and shoulder and elbow disorders in high school baseball pitchers. We surveyed 125 high school pitchers. Hip ROM was measured in the supine and prone positions. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Hamano et al demonstrated that preseason limited ROM of the hip with 90° flexed external rotation in the front leg was a risk factor for shoulder/elbow pain in the playing season 16 . In a cross-sectional study, these authors additionally reported that hip external rotation ROM on the back leg was significantly lower in injured high school baseball pitchers than in non-injured pitchers 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Hamano et al demonstrated that preseason limited ROM of the hip with 90° flexed external rotation in the front leg was a risk factor for shoulder/elbow pain in the playing season 16 . In a cross-sectional study, these authors additionally reported that hip external rotation ROM on the back leg was significantly lower in injured high school baseball pitchers than in non-injured pitchers 17 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Conventional physical therapy techniques, including hip mobility drills, stretching, gluteus medius/minimus strengthening, and dedicated core stability work have been suggested as essential elements of baseball athletic training for injury prevention, particularly among high school athletes in which pelvic and core stability may be relatively underdeveloped. 25,26…”
Section: Methodsmentioning
confidence: 99%
“…23 Decreased internal rotation ROM while the hip is at 90 degrees of flexion has been identified as a risk factor for shoulder, elbow, back, groin, abdominal, and hamstring injuries in baseball players. 20,[24][25][26] Reduced ROM or hip instability results in subtle, maladaptive compensation throughout the throwing motion, as force that is not properly transmitted throughout the kinetic chain places an increased burden on the distal elements, resulting in accumulation of damage through repeated activity. In addition, injuries to the ulnar collateral ligament (UCL) have been correlated with hip/groin pathology both prior to and after UCL surgery, and although the nature of this relationship is not well-understood, it provides further evidence that altered hip mechanics can be related to both proximal LE injuries and dysfunction of distal kinetic chain components.…”
Section: Hipmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Although the shoulder and elbow are common areas for symptom development, increased physiological stress on these joints can be produced by other remote regions in the body. 18,19 Risk factors such as glenohumeral internal rotation deficit (GIRD), [20][21][22][23][24] limited hip internal rotation ROM, 25-28 limited hip external rotation, 29 thoracic spine mobility, 30 total shoulder ROM, [22][23][24][31][32][33] and dynamic single leg balance 34 have been identified during comprehensive pre-season examinations and can result in time loss from sport.…”
Section: Introductionmentioning
confidence: 99%